PENGARUH PEMBERIAN MINYAK HATI IKAN PADA PAKAN BUATAN DENGAN DOSIS YANG BERBEDA TERHADAP PERTUMBUHAN BENIH IKAN KOI (CYPRINUS CARPIO): The Effect of Giving Fish Liver Oil In Artificial Feed With Different Dosages On Seed Growth Koi Fish (Cyprinus Carpio) - Irwan Faezan; Kurniawati Kurniawati; Aryani Rahmawati; I Gede Nano Septian (Yayasan Al-Amin Qalbu, 2023)
The purpose of this study was to determine the effect of giving fish liver oil to feed on the growth of koi ornamental fish seeds with different doses. The method used in this study is an experimental method using a completely randomized design. As for the treatment in M1 = without fish liver oil, M2 = with a dose of one tablespoon, M3 = with a dose of two tablespoons. Each treatment was repeated 3 (three) times to obtain 9 (nine) experimental plots. The feed dose given is 20%/BB/day. The amount of feed given during the study was 20.10 kg with a total of nine plots, all plots were given the same feed dose the only difference was the amount of fish liver oil mixture given. The highest average percentage of growth in weight of koi fish seeds was obtained in treatment M2, namely 1 tablespoon/day with an average value of 51.6% and the lowest was obtained in the treatment without fish liver oil (M1) with an average value of 15.3%. The results of the analysis of variance (ANASRA) showed a very significant difference where F count > F table 1% (48.4 > 10.92). Based on further tests using the least significant difference test (LSD) showed that the M1 and M2 treatments were highly significant (30.0> BNT = 14.46), the M1 and M3 treatments were not significantly different (6.30 <BNT = 14.46) , the treatment of M2 and M3 was very significantly different (36.3>BNT=14.46).